Preparation process and application of ultrathin damping conductive foam
By selecting specific conductive polymers and nano-scale conductive carbon black in the preparation process of shock-absorbing conductive materials, and combining environmentally friendly auxiliary materials, the preparation of ultra-thin shock-absorbing conductive foam is achieved, solving the shortcomings of existing materials in terms of performance stability and environmental protection, and significantly improving the reliability and service life of electronic equipment.
Patent Information
- Application Number
- CN202411876207.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing shock-absorbing conductive materials have shortcomings in preparation process, performance stability, application effect and environmental protection, and cannot meet the demand for high-performance shock-absorbing conductive components of electronic equipment.
The preparation process of ultra-thin shock-absorbing conductive foam is adopted. By selecting specific conductive polymers, nano-scale conductive carbon black and micro-scale metal powders as basic materials, and combining environmentally friendly auxiliary materials, precise mixing and plasticization, foaming and molding, curing and post-treatment are carried out to ensure the excellent conductive properties and shock absorption effect of the material.
It achieves a perfect combination of excellent conductivity and shock absorption effect, ensures the performance stability and environmental protection of the product, and is suitable for shock absorption and conductive components of electronic equipment, significantly improving the reliability and service life of the equipment.
Smart Images

Figure CN119650191A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new conductive shock-absorbing materials, and specifically discloses a preparation process and application of an ultra-thin shock-absorbing conductive foam. Background Art
[0002] As electronic devices become increasingly miniaturized and integrated, higher requirements are placed on the shock absorption and conductivity of components. Traditional shock absorption materials often have poor conductivity, while conductive materials often lack sufficient shock absorption effect, which limits the application of electronic devices in complex environments. In order to meet this demand, a variety of materials that attempt to combine shock absorption and conductive functions have appeared on the market, but these materials still have many deficiencies in preparation process, performance stability and application effect.
[0003] In the prior art, some shock-absorbing conductive materials use a simple physical mixing method to combine conductive fillers with shock-absorbing substrates. However, due to the poor compatibility between the fillers and the substrates, interface defects often exist inside the materials, affecting the conductivity and shock-absorbing effects. In addition, the preparation process of these materials often lacks precise control, resulting in poor product performance stability and failure to meet the needs of high-precision electronic equipment.
[0004] In addition, some traditional shock-absorbing conductive materials are prone to decline in conductivity and shock-absorbing effects during long-term use due to environmental factors (such as temperature and humidity changes), affecting the reliability and service life of electronic equipment. At the same time, these materials often use a large amount of organic solvents or produce harmful substances during the preparation process, posing a potential threat to the environment and human health.
[0005] In summary, the existing shock-absorbing conductive materials still have many shortcomings in terms of preparation process, performance stability, application effect and environmental protection, and cannot meet the urgent needs of electronic equipment for high-performance shock-absorbing conductive components. Therefore, it is particularly important to develop an ultra-thin shock-absorbing conductive foam and its preparation process with excellent conductive properties and shock-absorbing effect, precise and controllable preparation process, stable performance and environmental protection. Summary of the invention
[0006] To solve the above problems, we disclose a preparation process and application of ultra-thin shock-absorbing conductive foam.
[0007] The present invention includes the following specific technical solutions:
[0008] A preparation process of ultra-thin shock-absorbing conductive foam, comprising the following steps:
[0009] a) Raw material selection and pretreatment: Conductive polymers, conductive carbon black or metal powders are selected as base materials, and foaming agents, cross-linking enhancers, plasticizers and shock-absorbing performance enhancers are selected as auxiliary materials; the raw materials are pretreated to ensure purity and dispersion.
[0010] b) Mixing and plasticizing: Mix the base material and auxiliary materials according to the proportion, and use a twin-screw extruder or internal mixer to plasticize under controlled conditions to form a uniform mixture.
[0011] c) Foaming and molding: The mixture is injected into a mold, and foamed and molded into an ultra-thin foam blank by controlling heating and / or pressurizing conditions.
[0012] d) Curing treatment: The foam blank is subjected to heat curing, UV curing or chemical cross-linking treatment to ensure structural stability and conductive properties.
[0013] e) Post-processing and testing: Cut, trim, and surface treat the solidified foam, and test its electrical conductivity and shock absorption effects.
[0014] Furthermore, in the above-mentioned preparation process of the ultra-thin shock-absorbing conductive foam, the basic material includes a specific conductive polymer, nano-scale conductive carbon black and micron-scale metal powder.
[0015] Furthermore, in the above-mentioned process for preparing the ultra-thin shock-absorbing conductive foam, the auxiliary materials include an environmentally friendly foaming agent, a multi-functional cross-linking enhancer, a plasticizer and a shock-absorbing performance enhancer.
[0016] Furthermore, in the above-mentioned process for preparing the ultra-thin shock-absorbing conductive foam, in step b), a device with temperature control and shear force adjustment functions is used to mix and plasticize the materials.
[0017] Furthermore, in the above-mentioned preparation process of ultra-thin shock-absorbing conductive foam, in step c), the foaming degree and density of the foam are controlled by controlling the temperature, pressure and residence time of the mold, and adjusting the amount of the foaming agent and the foaming conditions.
[0018] Furthermore, in the above-mentioned preparation process of the ultra-thin shock-absorbing conductive foam, in step d), a precisely controlled curing technology is adopted, such as precise temperature control in thermal curing, high-efficiency light source in ultraviolet curing, or precise catalyst dosage control in chemical cross-linking.
[0019] Furthermore, the above-mentioned preparation process of the ultra-thin shock-absorbing conductive foam also includes the step of conducting a long-term performance test on the ultra-thin shock-absorbing conductive foam to evaluate its performance stability under different environmental conditions.
[0020] In the above preparation process of ultra-thin shock-absorbing conductive foam, through verification of the examples, we selected conductive polymers (such as polyacetylene), nano-conductive carbon black, micron-sized metal powder (such as spherical silver powder), environmentally friendly foaming agents (such as azodicarbonamide), multifunctional cross-linking enhancers (such as trimethylolpropane triacrylate), plasticizers (such as dioctyl phthalate), shock-absorbing performance enhancers (such as ethylene-vinyl acetate copolymers) and other additives (such as antioxidants, processing aids) and other raw materials. These raw materials each play a key role, and through scientific proportions and synergistic effects, the foam is comprehensively improved in terms of conductivity, shock absorption, mechanical properties and thermal stability. Conductive polymers, nano-scale conductive carbon black and micron-scale metal powder together construct an efficient conductive network, ensuring the excellent conductive properties of the foam; environmentally friendly foaming agents make the foam material expand and foam to form a porous structure, achieving good shock absorption effects; multi-functional cross-linking enhancers enhance the mechanical strength and heat resistance of the foam; plasticizers improve the flexibility and plasticity of the foam; shock absorption performance enhancers further enhance the shock absorption performance of the foam; and other additives help extend the service life of the foam.
[0021] Furthermore, the present invention also discloses an ultra-thin shock-absorbing conductive foam produced by the above process.
[0022] The invention also discloses the application of the ultra-thin shock-absorbing conductive foam in shock-absorbing conductive components of electronic equipment.
[0023] The present invention also discloses a shock-absorbing conductive component of an electronic device, comprising:
[0024] a) an ultra-thin shock-absorbing conductive foam layer, composed of the foam according to claim 8;
[0025] b) Conductive connecting parts, used for electrical connection with other electronic components or circuits;
[0026] c) a fixing structure for fixing the ultra-thin shock-absorbing conductive foam layer and its conductive connecting components inside the electronic device;
[0027] d) Optional protective layer to provide additional mechanical protection, water and dust resistance.
[0028] Compared with the prior art, the present invention has the following outstanding beneficial effects:
[0029] The present invention provides a preparation process of ultra-thin shock-absorbing conductive foam, which achieves a perfect combination of excellent conductive performance and shock-absorbing effect by selecting specific conductive polymers, nano-level conductive carbon black and micron-level metal powder as basic materials, and combining environmentally friendly auxiliary materials. The use of equipment with temperature control and shear force regulation functions for precise mixing and plasticization, as well as the precise control of the foaming degree and density of the foam achieved by precise control of mold conditions and the amount of foaming agent, ensures the consistency and stability of the product. At the same time, the use of precisely controlled curing technology and long-term performance testing steps ensures the stability of the foam structure, the durability of the conductive performance and the performance stability under different environmental conditions. In addition, the preparation process of the present invention is environmentally friendly and sustainable, reducing the use of organic solvents and the generation of harmful substances. Therefore, the prepared ultra-thin shock-absorbing conductive foam has a wide range of application prospects in electronic devices. As a shock-absorbing conductive component, it can significantly improve the reliability and service life of the equipment, providing strong support for the innovative development of electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Comparison results of shock absorption efficiency (%);
[0031] Figure 2 Comparison results of mechanical properties tests;
[0032] Figure 3 Comparative results of thermal stability tests. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The formula table of the embodiment of the present invention is shown in Table 1.
[0035] Table 1 Ultra-thin shock-absorbing conductive foam formula
[0036]
[0037] The preparation process of ultra-thin shock-absorbing conductive foam is as follows:
[0038] 1. Raw material selection and pretreatment
[0039] Raw material selection: select basic materials such as specific conductive polymers, nano-grade conductive carbon black, micron-grade metal powder, and auxiliary materials such as foaming agents, cross-linking enhancers, plasticizers, and shock-absorbing performance enhancers according to the formula table.
[0040] Pretreatment: Pretreatment of raw materials, including removal of impurities, drying (such as drying conductive carbon black and metal powder in a drying oven at 80-120°C for 2-4 hours) to ensure purity and dispersibility.
[0041] 2. Mixing and plasticizing
[0042] Equipment selection: Use a twin-screw extruder for mixing and plasticizing.
[0043] Process parameters:
[0044] Temperature control: screw zone 1 temperature 160-180℃, zone 2 temperature 180-200℃, zone 3 temperature 200-220℃, zone 4 temperature 220-240℃.
[0045] Shear force regulation: Shear force is controlled by adjusting the screw speed (e.g. 50-100 rpm) and the feed rate to ensure that the raw materials are fully mixed and not overly degraded.
[0046] Mixing time: Depending on the equipment model and raw material characteristics, the mixing time is 5-10 minutes.
[0047] 3. Foaming and molding
[0048] Mold preparation: Select a suitable mold and ensure that the mold temperature, pressure and dwell time are controllable.
[0049] Process parameters:
[0050] Mold temperature: According to the raw material formula and the required foam density, the mold temperature is set to 150-180℃.
[0051] Injection pressure: According to the raw material viscosity and mold structure, the injection pressure is set to 80-120MPa.
[0052] Residence time: The residence time in the mold is set to 30-60 seconds according to the decomposition rate of the foaming agent and the required cell structure.
[0053] Amount of foaming agent: Accurately weigh and add the foaming agent according to the range value in the formula table.
[0054] 4. Curing treatment
[0055] Selection of curing method: According to the raw material characteristics in the formula table, select the appropriate curing method, thermal curing;
[0056] Process parameters:
[0057] Thermal curing: carried out in an oven or on a heating plate, with the temperature set at 180-220°C for 20-40 minutes.
[0058] Examples 1-3
[0059] The specific formula of the ultra-thin shock-absorbing conductive foam is shown in Table 2.
[0060] Table 2 Specific formula of ultra-thin shock-absorbing conductive foam
[0061]
[0062]
[0063] The preparation process is shown in the specific implementation manner.
[0064] Comparative Examples 1-3
[0065] The specific formulas of the ultra-thin shock-absorbing conductive foams of Comparative Examples 1-3 are shown in Table 3.
[0066] Table 3 Specific formula of ultra-thin shock-absorbing conductive foam in comparative example 1-3
[0067]
[0068]
[0069] In Comparative Example 1, the conductive polymer was replaced by polyaniline, and the addition amounts of other raw materials were kept unchanged (except for the replacement items).
[0070] In Comparative Example 2, the conductive polymer was replaced by polythiophene, and the nano-scale conductive carbon black was replaced by carbon nanotubes, and the addition amount of some auxiliary materials was adjusted to optimize the performance.
[0071] In Comparative Example 3, the conductive polymer was replaced with polypyrrole, and the micron-sized metal powder was replaced with copper powder from silver powder. At the same time, the amount of auxiliary materials added was further adjusted to explore different performances.
[0072] The preparation process is the same as that of Examples 1-3.
[0073] Comparative Example 4
[0074] Commercially available ultra-thin shock-absorbing conductive foam.
[0075] Test Case
[0076] 1. This test scheme is intended to comprehensively evaluate the comprehensive performance of the ultra-thin shock-absorbing conductive foams prepared in Examples 1-3 and Comparative Examples 1-3 in terms of conductivity, shock-absorbing performance, mechanical properties and thermal stability.
[0077] 2. Test Sample Preparation
[0078] Sample cutting: Use precision cutting equipment to uniformly cut the ultra-thin shock-absorbing conductive foam prepared in each embodiment and comparative example into a shape of 25 x 25 x 1 (thickness) mm, ensuring that the thickness of all samples is consistent in each test to facilitate accurate comparison of the test results.
[0079] Sample marking: uniquely number each cut sample, and record in detail the corresponding example or comparative example number, as well as the specific size and thickness after cutting.
[0080] 4. Conductivity test
[0081] Test standard: Refer to ASTM D257-09 "Test method for DC resistance or conductivity" for testing.
[0082] Test method: Use the four-probe method or the two-probe method to measure the resistance value of the sample, and calculate its conductivity based on the size and thickness of the sample. Before testing, ensure that the sample surface is clean and free of dirt, and the test environment is kept at a constant temperature and humidity to reduce the impact of external factors on the test results. Test results: Conductivity (Siemens per meter, S / m)
[0083] 5. Shock absorption performance test
[0084] Test standard: Refer to the relevant clauses in ISO 8302-1:2011 "Vibration and shock isolators - Performance test methods".
[0085] Test method: Use a drop weight impact tester or vibration table to apply a certain amount of impact or vibration to the sample, and use a sensor to record the acceleration change of the sample during the force process, and then calculate its shock absorption efficiency. During the test, it is necessary to ensure that the sample is installed firmly, and the direction of the impact or vibration is consistent with the main force direction of the sample. Test results: shock absorption efficiency (%).
[0086] 6. Mechanical properties test
[0087] Test standard: Tested in accordance with ASTM D638-14 "Test method for tensile properties of plastics".
[0088] Test method: Place the sample on a universal material testing machine and perform a tensile test at a constant speed. Record the stress-strain curve of the sample during the stretching process, as well as the maximum stress and elongation at break at break. Before testing, ensure that the sample has no initial stress or deformation in the test direction. Test results: Maximum stress (MPa), elongation at break (%).
[0089] 7. Thermal stability test
[0090] Test standard: Refer to ASTM E1131-19 "Guide to Thermogravimetric Analysis of Materials".
[0091] Test method: Use a thermogravimetric analyzer (TGA) to heat the sample and record the curve of the sample mass changing with temperature. Evaluate the thermal stability of the sample by analyzing the key temperature points in the curve (such as the initial decomposition temperature, the maximum weight loss temperature, etc.). During the test, ensure that the sample is fully dry and the test environment is free of interfering substances. Test results: Initial decomposition temperature (℃).
[0092] The test results are shown in Table 4-7.
[0093] Table 4 Conductivity test
[0094] Example / Comparative Example Conductivity (S / m) Example 1 1.24×10^5 Example 2 1.35×10^5 Example 3 1.38×10^5 Comparative Example 1 0.82×10^5 Comparative Example 2 1.05×10^5 Comparative Example 3 1.11×10^5 Comparative Example 4 1.15×10^5
[0095] Table 5 Shock absorption performance test
[0096] Example / Comparative Example Shock absorption efficiency (%) Example 1 68.3 Example 2 70.2 Example 3 72.7 Comparative Example 1 55.4 Comparative Example 2 60.5 Comparative Example 3 62.1 Comparative Example 4 57.5
[0097] Table 6 Mechanical properties test
[0098]
[0099]
[0100] Table 7 Thermal stability test
[0101]
[0102] According to the detailed data comparison of Tests 1-4, we can clearly see that Examples 1-3 have shown significant advantages in multiple key performance indicators. In the conductivity test, the conductivity of Examples 1-3 is higher than that of Comparative Examples 1-3, and even exceeds that of the commercially available product Comparative Example 4, which shows that our materials have excellent capabilities in current transmission and provide more stable and efficient solutions for applications that require high conductivity, such as electronic devices and conductive films. At the same time, in the shock absorption performance test, the shock absorption efficiency of Examples 1-3 is also higher than that of the comparative example, which once again proves the superiority of our materials in impact absorption and energy dissipation, which is undoubtedly a huge improvement for applications such as sports equipment and automotive parts that require shock absorption protection. In addition, the results of the mechanical properties test also show that Examples 1-3 perform well in both maximum stress and elongation at break. The strong mechanical properties make our materials more durable and reliable when subjected to external forces, and are suitable for scenes that require high strength and high toughness, such as building materials and mechanical parts. Finally, in the thermal stability test, the initial decomposition temperature and maximum weight loss temperature of Examples 1-3 are higher than those of the comparative example, and the mass loss percentage is lower, which fully demonstrates the stability of our materials in high temperature environments and provides reliable protection for high temperature application scenarios such as high temperature sensors and thermal protection materials. In summary, Examples 1-3 have shown significant beneficial effects in terms of electrical conductivity, shock absorption, mechanical properties and thermal stability. These advantages not only surpass certain products on the market, but also provide broad prospects and huge potential for the application of our invention in multiple fields.
[0103] The above are only a few preferred embodiments of the present invention, which are described in a more specific and detailed manner, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A preparation process of ultra-thin shock-absorbing conductive foam, characterized in that: The following steps are involved: a) Raw material selection and pretreatment: Select conductive polymers, conductive carbon black or metal powder as the base material, and select foaming agents, cross-linking enhancers, plasticizers and shock-absorbing performance enhancers as auxiliary materials; pre-treat the raw materials to ensure purity and dispersion; b) Mixing and plasticizing: Mix the base material and auxiliary materials according to the proportion, and use a twin-screw extruder or internal mixer to plasticize under controlled conditions to form a uniform mixture; c) Foaming and molding: injecting the mixture into a mold, foaming it and molding it into an ultra-thin foam blank by controlling heating and / or pressurizing conditions; d) Curing: The foam blank is thermally cured, UV-cured or chemically cross-linked to ensure structural stability and conductive properties; e) Post-processing and inspection: Cut, trim, and surface treat the solidified foam, and inspect its electrical conductivity and shock absorption effects.
2. The process according to claim 1, characterized in that The basic materials include specific conductive polymers, nano-scale conductive carbon black and micron-scale metal powder.
3. The process according to claim 1, characterized in that The auxiliary materials include an environmentally friendly foaming agent, a multifunctional cross-linking reinforcing agent, a plasticizer and a shock-absorbing performance enhancing agent.
4. The process according to claim 1, characterized in that In step b), the materials are mixed and plasticized using equipment with temperature control and shear force regulation functions.
5. The process according to claim 1, characterized in that In step c), the foaming degree and density of the foam are controlled by controlling the temperature, pressure and residence time of the mold, and adjusting the amount of the foaming agent and the foaming conditions.
6. The process according to claim 1, characterized in that In step d), a precisely controlled curing technique is used, such as precise temperature control in thermal curing, a high-efficiency light source in ultraviolet light curing, or precise catalyst dosage control in chemical cross-linking.
7. The process according to claim 1, characterized in that It also includes steps for long-term performance testing of ultra-thin shock-absorbing conductive foam to evaluate its performance stability under different environmental conditions.
8. An ultra-thin shock-absorbing conductive foam made by the process described in any one of claims 1 to 7.
9. Application of the ultra-thin shock-absorbing conductive foam as claimed in claim 8 in shock-absorbing conductive components of electronic equipment.
10. A shock-absorbing conductive component for an electronic device, characterized in that: include: a) an ultra-thin shock-absorbing conductive foam layer, composed of the foam according to claim 8; b) Conductive connecting parts used to make electrical connections with other electronic components or circuits; c) a fixing structure for fixing the ultra-thin shock-absorbing conductive foam layer and its conductive connecting components inside the electronic device; d) Optional protective layer to provide additional mechanical protection, water and dust resistance.